A Heuristic Tool for Teaching Business Writing: Self-Assessment, Knowledge Transfer, and Writing Exercises. Issue 2 (June 2013) - Ortiz, Lorelei A.
To teach effective business communication, instructors must target students' current weaknesses in writing. One method for doing so is by assigning writing exercises. When used heuristically, writing exercises encourage students to practice self-assessment, self-evaluation, active learning, and knowledge transfer, all while reinforcing the basics of good writing. Using writing exercises as a diagnostic or maintenance tool at different stages in the semester, in addition to the core assignments, can drastically improve undergraduate and graduate student writing and increase the probability that these students will transfer that writing knowledge into other courses and into their practices as professional writers in industry.